2012
DOI: 10.1016/j.chemosphere.2012.05.071
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater Ulva (Chlorophyta) as a bioaccumulator of selected heavy metals (Cd, Ni and Pb) and alkaline earth metals (Ca and Mg)

Abstract: Freshwater Ulva (Chlorophyta) as a bioaccumulator of selected heavy metals (Cd, Ni and Pb) We analyzed the ability of freshwater taxa of the genus Ulva (Ulvaceae, Chlorophyta) to serve as bioindicators of metal in lakes and rivers. Changes in heavy metal (Ni, Cd and Pb) and alkaline earth metal (Ca and Mg) concentrations in freshwater Ulva thalli were investigated during the period from June to August 2010. The study was conducted in two ecosystems in Western Poland, the Malta lake (10 sites) and the Nielba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Recent studies of the Ulva taxa in European fresh waters have primarily employed molecular methods for correct species identification (Mareš et al, 2011), complementing determination of morphometric and ultrastructural characteristics Messyasz et al, 2013) and bioaccumulation of metals (Rybak et al, 2012a(Rybak et al, , 2012b. Similarities among Ulva flexuosa subspecies make identification of freshwater Ulva problematic, and there has been no complete account of their morphological characteristics or habitat niches.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of the Ulva taxa in European fresh waters have primarily employed molecular methods for correct species identification (Mareš et al, 2011), complementing determination of morphometric and ultrastructural characteristics Messyasz et al, 2013) and bioaccumulation of metals (Rybak et al, 2012a(Rybak et al, , 2012b. Similarities among Ulva flexuosa subspecies make identification of freshwater Ulva problematic, and there has been no complete account of their morphological characteristics or habitat niches.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the studied organic compounds had a negligible effect on the development of algae and their biomass composition in contrast to the metal ions [2][3][4][6][7][8]14,15], inorganic phosphorus [22,23] and nitrogen [16]. However, Berman & Chava [27] proved that also organic nitrogen sources might significantly stimulate the development of algae, especially when urea was the only nitrogen source.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that different inorganic molecules, especially metal ions [2][3][4][7][8][9][10][11][12][13][14][15], as well as inorganic phosphorus [22,23] and nitrogen from nitrates and ammonium salts [16], has a significant effect on the composition of algae biomass. In our studies, we focused on the impact of four organic compounds: ascorbic acid, biotin, glucose and sucrose, on ash, protein, fiber, fat and amino acid content in the freshwater Aegagropila linnaei biomass.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds contain hydroxyl, carboxyl, sulfhydryl, amide, and amine functional groups with high affinity to metal ions under certain conditions. The quantity and quality of these functional groups differ among microalgae, meaning that each algal species has a different metal-binding capability [1,7,11].…”
Section: Introductionmentioning
confidence: 99%